Possible causes of spatial variability in Diatraea saccharalis Fabr. (Lep., Crambidae) and its parasitoid populations in sugarcane fields in Brazil - Rossi, M. N. (Blackwell Verlag Gmbh, 2003)
Based on the large data set stored in some sugarcane mills regarding the biological control programme of Diatraea saccharalis using the parasitoids Cotesia flavipes and tachinid flies, the aim of the present study was to determine whether sugarcane varieties, number of cuts and plant ages are major determinants in promoting spatial variability in D. saccharalis, C. flavipes and tachinid fly populations in sugarcane fields in the state of São Paulo (Brazil). The data set used to support this study was provided by the Sao Joao and Barra sugarcane mills. Coefficient of variation was adopted as a measure of the spatial variability of population density. Spatial variability was estimated for the total density of D. saecharalis (parasitized + unparasitized larvae), and also for D. saccharalis larvae parasitized by tachinids and by C. flavipes. Statistical analysis revealed that the spatial variation in D. saccharalis populations was influenced by the number of cuts and by plant ages in the Barra and Sao Joao Mills, respectively. Similar results were obtained for D. saccharalis larvae parasitized by tachinids; however, in the Sao Joao Mill, the spatial variability of these populations was also influenced by the different number of varieties. Finally, considering D. saccharalis larvae parasitized by C. flavipes, no significant regressions with any of the three categories were observed for both sugarcane mills. The multitrophic implications for this agricultural system are also discussed.
Keywords: Cotesia flavipes; Diatraea saccharalis; biological control; spatial variability; tachinid flies